Numerical analysis of free convection from a spinning cone with variable wall temperature and pressure work effect using MD-BSQLM - Makanda Gilbert (De Gruyter, 2021)
The problem of the numerical analysis of natural convection from a spinning cone with variable wall temperature, viscous dissipation and pressure work effect is studied. The numerical method used is based on the spectral analysis. The method used to solve the system of partial differential equations is the multi-domain bivariate spectral quasi-linearization method (MD-BSQLM). The numerical method is compared with other methods in the literature, and the results show that the MD-BSQLM is robust and accurate. The method is also stable for large parameters. The numerical errors do not deteriorate with increasing iterations for different values of all parameters. The numerical error size is of the order of 10−101{0}^{-10}. With the increase in the suction parameter ξξ , fluid velocity, spin velocity and temperature profiles decrease.